Ethnoscience of Tengger Tribes in Bromo Tengger Semeru National Park Area on Ecosystem Material to Support Education for Sustainable Development - Maftuha, Mahda Rizqina; Sriyati*, Siti; Solihat, Rini; Nisrina, Nisrina (Universitas Syiah Kuala, 2025)
The implementation of the Tengger tribe's local wisdom in biology learning was known still limited, particularly in Pasuruan. Science learning based on local wisdom can strengthen students' understanding by enhancing their interpretive abilities in interpreting natural phenomena and symptoms. The philosophical values of local wisdom can reflect, provide positive direction for students in learning, and innovate in efforts to support educational for sustainable development (ESD). Method used in this research was qualitative with data collection methods are literature studies, observation, and interviews. The sampling technique used was purposive sampling. Data processing technique uses data triangulation. There are four main findings: 1) Analysis of the correlation between Tengger tribe's local wisdom, science, ecosystem material, and learning objectives. 2) Collaboration of Tengger tribe with stakeholders. 3) Analysis of the implementation of ethnoscience and ESD in biology learning. 4) Implementation of the Tengger tribe's local wisdom in biology learning as an effort to support ESD. From the discussion, it was concluded that Tengger tribe's ethnoscience, the local potential of Bromo Tengger Semeru National Park, and collaboration of Tengger tribe with stakeholders have great potential to be used as student teaching materials in biology subjects on ecosystem material and as an effort to support ESD